FRI0387 Pain, health-related quality of life and health status in GOUT in europe. (23rd January 2014) - Langley, P.; Nuki, G.; Forsythe, A.
Abstract : Background: Gout is an increasingly prevalent rheumatic disease (with acute and chronic components) which is associated with significant reduction in Health-Related Quality of Life (HRQoL) 1, 2 . Although much of this impairment results from associated comorbidities 1, 2 recent expert consensus has emphasised the importance of measuring pain as a key patient reported outcome (PRO) in chronic gout 3 . Thus there remains a need to assess the independent impact of pain in gout populations. Objectives: To measure quantitatively the impact of pain, with particular reference to severe daily pain and chronic gout, on HRQoL in Western Europe using data from the National Health and Wellness Survey (NHWS). Methods: NHWS is a syndicated, annual and biannual, nationally representative, cross-sectional, internet-based study of the healthcare attitudes, behaviors, and characteristics of adults. Data from over 57, 000 respondents in the UK, France, Spain, Germany, and Italy, collected in 2010 was utilized. Respondents reporting physician-diagnosed gout in the prior 12 months were identified (n=756). Details of pain severity and frequency in the previous 30 days were recorded along with demographic and socio-economic characteristics and comorbidities. HRQoL was assessed using the SF-12 instrument (version 2, with a focus on the physical and mental component summary scores; PCS and MCS). Health state utilities were captured with the SF-6D scoring algorithm and self-reported health status (first item of SF-12 questionnaire). Multivariate regression analysis was performed to assess the contribution of severe daily gout pain vs other (non-gout) pain using a reference a group of patients diagnosed with gout who were pain-free. Results: The overall annual prevalence of gout in adults for the 5 countries was 1.28%. Among those diagnosed with gout, 34.89% reported experiencing pain in the last 30 days (vs. 19.95% of controls in the NHWS cohort who did not report gout; p<0.05); 25.08% (vs. 16.74% of controls; p<0.05) of patients with pain reported severe pain (equivalent to approximately 8% of the gout population), and 22.93% (vs. 13.47% of controls; p<0.05) reported severe daily pain. Compared with the reference group of persons with gout not reporting pain, the effect of severe daily pain on PCS (-15.29; 95% CI -17.6, -13.0) and MCS (-5.35; 95% CI -8.1, -2.6) was significant. It was substantially greater than other pain (severe non-daily pain, moderate pain, mild pain) which were collapsed into a single variable (PCS: -6.0; 95% CI -7.5, -4.5). The impact of other pain experience on MCS was not significant. The influence of pain on SF-6D utilities was also striking; for daily severe pain the deficit was -0.17 (95% CI -0.20, -0.14) while other pain generated a deficit of -0.05 (95% CI -0.07, -0.03). Conclusions: A survey of patient-reported pain in patients diagnosed with gout in Western Europe has demonstrated that daily pain is a characteristic of chronic gout, and is associated with substantial deficits in HRQoL and self-reported health status. The estimate that 1 in 5 gout patients experience moderate or severe daily pain, presents an important challenge for physicians. References: Roddy E et al. Rheumatol 2007; 46:1441-6. Singh JA et al. Ann Rheum Dis 2008; 67(9):1310-6. Singh JA et al. J Rheumatol 2011; 38:1452-7. Disclosure of Interest: P. Langley Consultant for: Novartis, Pfizer, Kantar Health, Grunenthal, Johnson and Johnson, Shire, Bayer, Savient, G. Nuki Consultant for: Ardea, Menarini, Novartis, Savient, Paid Instructor for: Ipsen, Menarini, A. Forsythe Shareholder of: Savient, Novartis, Employee of: Novartis